The Effectiveness of Reading English Learning Process Based on Blended Learning through "Absyak" Website Media in Higher Education - Abd. Syakur; Zainal Fanani; Rulam Ahmadi (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
The fastest development of technology and the internet in the 4.0 revolution era that influenced the world of education, especially higher education. Currently education focuses on outcome-based education, thus forcing all lecturers to innovate in teaching and learning. One form is by on-line learning for English learning materials developed through the website. This study analyzes the effectiveness of on-line based learning on websites on the ability to read students in the process of learning English at Universitas Brawijaya through "absyak" media websites. The use of the blended learning model has been done in several subjects, but for English subjects (reading) has never been done before. This research is quantitative descriptive. The research sample used a sample of 65 students through a questionnaire on students of the English language study program at Brawijaya University in academic year 2018/2019. The results showed that 81.99% agreed with the application of English reading learning based on blended learning through "absyak" media websites and the remaining 18.01% did not agree on learning English reading based on blended learning through "absyak" media websites. The implementation of online-based learning through "absyak" learning in the media can be effectively contained in high student responses, increased student scores and student attitudes towards variation and learning innovation.